Clinical evaluation of the effect of a herbal compound made for treatment of discolorations caused by dental fluorosis - Mahshid Mohammdi Basir; Elham Tabatabai Ghomsheh; Mohammad Bagher Rezvani; Zeinab Rafie; Zahra Malek Hoseini (Tehran University of Medical Sciences, 2013)
Background and Aims: The purpose of this study was research on a new herbal compound (Seidlitzia Rosmarinus) made by Traditional Medicine Research Group, University of shahed to find a safer alternative to HCL-Pumice compound technique.   Materials and Methods: In this randomized clinical trial seventy two anterior teeth from 9 patients were divided in to three groups according to fluorosis severity: mild (34 teeth), moderate (14 teeth), and sever (24 teeth). In each patient, half of the teeth were treated with "Shahed" compound and other half treated with HCL-Pumice compound. Before and after treatment, photographs were taken in both groups. HCL-Pumice treatment compound was applied for 30 seconds periods and continued for 10 minutes if necessary. In case of herbal Shahed compound the time was determined by clinical symptoms or when labial contour was dismissed, If the result was not esthetistically acceptabale for the patient, HCL-Pumice compound was applied on teeth. NaF was applied after mouth washing. The photographs of the teeth before and after treatment were reviewed by two experienced observer unaware of the treatment modality. The results were analyzed using willcoxon's, kruskal-wallis and scheffe test.   Results: There was over 81.3% acceptance between two observers and no significant differences in intraobservers evaluation (P>0.05). Improvement in beauty indexes were observed in all degrees of dental fluorosis by 18% with HCL-Pumice compound application, but "Shahed" herbal compound induced significant reduction in the amount of white spots in mild fluorosis and stain intensity of moderate fluorosis (P<0.05) , while the reduction in the severity of discoloration in group 2, these two techniques were statistically equivalent but in the remainder, HCL-Pumice compound was more significantly effective (P<0.05) .   Conclusion: HCL-Pumice compound reduces the severity of the discoloration of the teeth. Shahed herbal compound cannot reduces the discoloration like as HCL-Pumice compound.